2005
DOI: 10.1038/nmat1403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of ultrahigh-strength gold nanowires

Abstract: Nanowires have attracted considerable interest as nanoscale interconnects and as the active components of both electronic and electromechanical devices. Nanomechanical measurements are a challenge, but remain key to the development and processing of novel nanowire-based devices. Here, we report a general method to measure the spectrum of nanowire mechanical properties based on nanowire bending under the lateral load from an atomic force microscope tip. We find that for Au nanowires, Young's modulus is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

34
677
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 895 publications
(718 citation statements)
references
References 28 publications
34
677
4
3
Order By: Relevance
“…the magnitude of compressive yield stress decreases as the nanowire width increase. These size effect trends are in good agreement with the experimental reports in the literature [25], in which the diameterdependent yield stress of gold nanowires with size ranging from 40 to 200 nm measured by means of bending experiments was reported [25]. The yield stresses of Ni nanowires reported here are substantially greater than that of bulk Ni, but close to the theoretical stress, which is 30 GPa from experiments [26].…”
supporting
confidence: 91%
“…the magnitude of compressive yield stress decreases as the nanowire width increase. These size effect trends are in good agreement with the experimental reports in the literature [25], in which the diameterdependent yield stress of gold nanowires with size ranging from 40 to 200 nm measured by means of bending experiments was reported [25]. The yield stresses of Ni nanowires reported here are substantially greater than that of bulk Ni, but close to the theoretical stress, which is 30 GPa from experiments [26].…”
supporting
confidence: 91%
“…For all the experiments carried out with this setup, the distance between the needle and the collector was set at Solutions were electrospun for a very short time (~45 s), resulting in a low density mesh of fibers with radii between 20 and 40 nm. Mechanical measurements were performed following a technique previously developed for metallic and semiconducting wires (25)(26)(27). Scanning electron microscopy was used to monitor both the density and the position/alignment of the nanofibers across the trenches.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscopy was used to monitor both the density and the position/alignment of the nanofibers across the trenches. Fibers spanning the trenches perpendicularly were pinned down by electron beam induced deposition of platinum inside a scanning electron microscope chamber (25) as shown on Figure 1A. Both the diameter and suspended length were measured for all fibers using an atomic force microscope (AFM).…”
Section: Methodsmentioning
confidence: 99%
“…It scales as j / h 2/3 h. [22] For our case, a gold film (Y gold % 78 GPa) on a PS substrate (Y PS % 3.5 GPa), we anticipate h ¼ Y gold /Y PS % 22.3. [23,24] To verify the theoretical predictions, we varied the thickness of deposited gold from 10 nm to 50 nm. This caused a shift of hundreds of nanometers in the wavelength distributions (Fig.…”
mentioning
confidence: 99%
“…[25] For example, yield strengths of gold nanowires (3-6 GPa) are much greater than that of the bulk (55-200 MPa). [23] In particular, for metallic nanofilms on polymer substrates, most groups have found that the yield stress scales inversely with the film thickness, with the most recently measured yield stress value for a 50 nm gold film (which happens to be our highest film thickness) on PS substrates being as high as 30 GPa. [26] Thus, for the film thicknesses we use, our peak stresses are clearly well below the yield point -which means that predictions from linear elasticity theory are appropriate.…”
mentioning
confidence: 99%